2004
DOI: 10.1038/ncb1152
|View full text |Cite
|
Sign up to set email alerts
|

MLK3 is required for mitogen activation of B-Raf, ERK and cell proliferation

Abstract: The ERK group of mitogen-activated protein kinases (MAPKs) is essential for cell proliferation stimulated by mitogens, oncogenic ras and raf (ref. 1). All MAPKs are activated by MAP3K/MEK/MAPK core pathways and the Raf proto-oncoproteins, especially B-Raf, are ERK-specific MAP3Ks (refs 1-3). Mixed lineage kinase-3 (MLK3) is a MAP3K that was thought to be a cytokine-activated, and comparatively selective, regulator of the JNK group of MAPKs (refs 1, 4-6). Here we report that silencing of mlk3 by RNAi suppressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
190
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(204 citation statements)
references
References 27 publications
9
190
5
Order By: Relevance
“…In contrast, CEP-11004 treatment inhibited MLK3 induced ERK activation (Fig. 4C), which is consistent with a role for MLK3 in activating the ERK pathway in tumor cells [14]. This further supports the opposing roles for MLK3 in promoting proliferation of non-neuronal tumor cells but cell death of neuronal cells.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In contrast, CEP-11004 treatment inhibited MLK3 induced ERK activation (Fig. 4C), which is consistent with a role for MLK3 in activating the ERK pathway in tumor cells [14]. This further supports the opposing roles for MLK3 in promoting proliferation of non-neuronal tumor cells but cell death of neuronal cells.…”
Section: Discussionsupporting
confidence: 82%
“…MLK3 function in cell death has been largely attributed to its role in activating the stress activated protein kinases, which include JNK and p38 [1]. However, recent studies also show that MLK3 can mediate cell proliferation through activation of the B-Raf and ERK pathway [14]. To identify mechanisms by which MLK proteins may affect cell proliferation, we examined the effects of MLK inhibition during G2-phase on subsequent progression through mitosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, MLK3 knockout mice have reduced JNK activation in response to TNF␣ (Brancho et al, 2005). B-raf/ERK activation by mitogens is also regulated by MLK3 (Chadee and Kyriakis, 2004), but this is apparently dispensable during development. Of the known MLKs, MLK3 and MLK7 are detected in the adult heart (Bloem et al, 2001).…”
Section: Mlk (Omim#*600136 [Mlk1] *600137[mlk2] *600050[mlk3])mentioning
confidence: 99%
“…Nonetheless, mammalian MLK3 is localized to the centrosome, and its activity is enhanced during G 2 /M phase transition, when the JNK pathway remains inactive (23). It has been reported that silencing MLK3 can block mitogen-stimulated B-Raf activation and prevent serum-or Ki-Ras-stimulated cell proliferation (24). In addition, MLK2 has been involved in modulation of NeuroD and Alien transcription factors (25,26).…”
mentioning
confidence: 99%